Facteurs alimentaires et environnementaux de risque du cancer du rhino-pharynx dans la région de Marrakech - Soumia Ammor; Abdellatif Baali; Annie Hubert; Mohamed Cherkaoui (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In Morocco, as in the other countries of the Maghreb, NPC is the most frequent cancer of the ORL sphere.The distribution by age and sex of a sample composed by 160 cases diagnosed between 1989 and 1999 in Marrakech hospitals has shown that men are more affected than women with a sex-ratio of 2,6 and that the proportion of the individuals younger than 25 years and affected by the NPC is 20%. Women are affected earlier than men: a peak has been observed between the ages of 20 and 30 in women and another between the ages of 40 and 50 in men.The analysis of a questionnaire submitted to 32 individuals affected by the NPC and to a check sample of 48 showed a statistically significant relationship between the NPC and some nutritional and environmental factors: consumption of smen (fermented butter), khlii (dried, salted spicy baked meat preserved in a mixt of smelted beef grease) and alcohol; practising of agriculture and cattle breeding; contact with toxic substances.